Histopathologic Study of Caries at the Full and Partial Crowns Finish Line - A Akhavan Tafti (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: The cast crowns replace lost tooth structure. Probably, recurrent caries occurs at the preparation margins and give rise to crown failure, affected by several factors, such as dental prosthesis design. The aim of this study was to investigate and compare of dental caries depth at full and partial crown margins. METHODS: In this experimental study, eighteen sound human maxillary premolars were assigned randomly into three groups (control, partial and full), prepared based on standard preparation and crowned under a 5-Kg load. After marginal adaptation assessment, the crowns were exposed to a demineralizing solution (pH 4.5) for 10 days. Then crowns were debounded and teeth were decalcified in 5% nitric acid. Each margin was serially sectioned into a thickness of 5 µm. For depth of lesion evaluating, light microscopy (40X magnification), with 0.001 mm accuracy, was used.FINDINGS: No significant difference was observed between mean caries value of full crowns and partial crowns (289.026±250.207 µm vs. 276.688±180.513 µm). Vertical margins of partial crowns presented higher mean value of caries depth than horizontal margins of these crowns (p= 0.03). But, due to less vertical margins, only 31% of total partial crown caries was assigned to those. CONCLUSION: According to the results, although, despite to higher margins in partial crown, there is no difference in secondary caries between partial and full crowns. In conclusion, when some of axial tooth walls are intact, partial crown is more beneficial to preserve tooth structure and aesthetics.